PENERAPAN HFSM PADA GAME 3D “PETUALANG QUR’AN” - Juniardi Nur Fadila; Fresy Nugroho; Vera Artanti; Salma Ainur Rohma; Muhammad Khoirul Huda; Nur Syamsu Priambudi (LPPM Universitas Putera Batam, 2023)
Game is a game that is very liked by children and adults. In making this game the author applies Islamic learning, namely Adventurers of the Qur'an. In making this game, the author uses the Hirarchical Finite State Machine (HFSM) method. This game is an adventure in a forest, countryside, road and river. When the player is on an adventure, he will find a Qur'an quiz that must be answered and solved. When the player cannot answer and cannot pass the Non Playable Character (NPC), the game will repeat to the initial start. In this game there are four Non Playable Character (NPC), namely Small Parasites, Boats, Vehicles and Pigs. The four Non Playable Character (NPC) can make decisions on what to do with players. The decision making of the four Non Playable Character (NPC) is implemented using the Hirarchical Finite State Machine (HFSM) method using the Unity game engine.